A systematic approach to measure the contents of mono- and di-sulfonates in petroleum sulfonates by the novel method of acid–base titration coupled with traditional two-phase titration. Issue 67 (15th November 2018) - Duan, Yawei; Feng, Jingge; Zhu, Youyi; Li, Hongda; Liu, Xintong; Zhou, Hualei; Li, Wenjun
Abstract : This study established a systematic, reduced cost and high universality approach to measure the contents of mono- and di-sulfonates in petroleum sulfonates by the novel method of acid–base titration coupled with traditional two-phase titration. Abstract : Petroleum sulfonates are broadly employed to increase the oil recovery efficiency in tertiary recovery, while the content of di-sulfonates in petroleum sulfonates is a critical factor in the flushing efficiency, because it adversely impacts the decrease of oil-water interfacial tension. Thus far, no methods have been considered convenient and reliable to determine the contents of mono- and di-sulfonates besides the traditional extraction method. This study established a simple and practical approach of acid–base titration coupled with traditional two-phase titration to measure the contents of mono- and di-sulfonates in petroleum sulfonates. To judge the reliability of the approach, the actives of petroleum sulfonates were separated into mono- and di-sulfonates using the traditional extraction method, the separation effect of which was confirmed using infrared spectroscopy and main elemental analysis. As the results demonstrated, all the contents of di-sulfonates in four petroleum sulfonates measured by the acid–base titration method are similar to those found by the extraction method. The contents of di-sulfonates (%) in four petroleum sulfonate samples were measured by comparing acid–base titration with the extraction method; respectively they were 8.57/8.19, 5.67/5.98, 5.61/5.35 and 2.37/2.15; the relative error of the measured di-sulfonates is about 6%, which satisfies the titration accuracy of petroleum sulfonates. In parallel experiments, the results of five acid–base titrations are very close, and the precision of the acid–base titration method was about 3%. Accordingly, this systematic approach by combining the new acid–base titration and traditional two-phase titration is of great significance to develop the evaluation system of petroleum sulfonates.